C-IEDD metacognitive requisite ratings - Smy, Victoria; Witheridge, Annamaria; Clewley, Natalie; Dodd, Lorraine (Cranfield University, 2021)
Red/amber/green (RAG) analysis of metacognitive requisites at key decision points throughout a challenging counter-improvised explosive device disposal incident.
Keywords: 'Explosive ordnance device'; 'counter-improvised explosive device'; 'expertise'; 'metacognitive requisites'; 'Applied Psychology'; 'Decision Making'